2013
DOI: 10.1242/dev.088351
|View full text |Cite
|
Sign up to set email alerts
|

Zebrafish second heart field development relies on progenitor specification in anterior lateral plate mesoderm and nkx2.5 function

Abstract: SUMMARYSecond heart field (SHF) progenitors perform essential functions during mammalian cardiogenesis. We recently identified a population of cardiac progenitor cells (CPCs) in zebrafish expressing latent TGFβ-binding protein 3 (ltbp3) that exhibits several defining characteristics of the anterior SHF in mammals. However, ltbp3 transcripts are conspicuously absent in anterior lateral plate mesoderm (ALPM), where SHF progenitors are specified in higher vertebrates. Instead, ltbp3 expression initiates at the ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
86
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(92 citation statements)
references
References 62 publications
(131 reference statements)
5
86
1
Order By: Relevance
“…However, downregulated expression of ltbp3, an SHF marker (Zhou et al, 2011), in nkx2.5 mutant embryos (supplementary material Fig. S8A,C) suggests that there could be diminished contribution from the SHF, consistent with a recent report demonstrating reduced ltbp3 expression and reduced production of SHF-derived cardiomyocytes in embryos injected with an anti-nkx2.5 MO (Guner-Ataman et al, 2013 Fig. S8E), further highlighting the impact of Nkx gene function on regulation of ltbp3.…”
Section: Transformation From Ventricular To Atrial Identity In the Absupporting
confidence: 86%
“…However, downregulated expression of ltbp3, an SHF marker (Zhou et al, 2011), in nkx2.5 mutant embryos (supplementary material Fig. S8A,C) suggests that there could be diminished contribution from the SHF, consistent with a recent report demonstrating reduced ltbp3 expression and reduced production of SHF-derived cardiomyocytes in embryos injected with an anti-nkx2.5 MO (Guner-Ataman et al, 2013 Fig. S8E), further highlighting the impact of Nkx gene function on regulation of ltbp3.…”
Section: Transformation From Ventricular To Atrial Identity In the Absupporting
confidence: 86%
“…It was shown that, as in higher vertebrates, this region contributes to endocardial cells but only within the outflow tract region of the heart; no contribution to endocardial cells within the main chambers was detected. It was further shown, using Cre/loxP-mediated lineage tracing of GATA binding protein 4 + (gata4 + ) and nkx2.5 + cell populations, that zebrafish secondary heart field progenitors are specified within the ALPM and contribute to endocardial cells only within the outflow tract region of the heart (Guner- Ataman et al, 2013). In line with this, and in contrast to higher vertebrates in which secondary heart field-derived endocardial cells contribute to a large portion of the right ventricular endocardium (Cai et al, 2003;Milgrom-Hoffman et al, 2011;Moretti et al, 2006;Verzi et al, 2005), endocardial growth of the zebrafish main cardiac chambers is largely independent of a secondary heart field contribution (Lazic and Scott, 2011;Dietrich et al, 2014).…”
Section: Developmental Origins Of the Endocardiummentioning
confidence: 99%
“…(1) EdU staining does not require DNA denaturation and therefore preserves the integrity of tissue; (2) EdU staining may conserve antigenicities for molecular markers; (3) EdU staining is much faster than BrdU staining (Guner-Ataman et al 2013). Our current findings show that EdU robustly labeled dividing cardiac cells in vitro and in vivo.…”
Section: Discussionmentioning
confidence: 64%